Novel Perspectives on Communication Practices in Antiquity
1 online resource
Keywords: Documentary texts are vital to our understanding of many aspects of the ancient world, such as its administration, education, and economy. The value of these texts goes even further however: being autographs, they directly testify to ancient communication practices, a field of study which so far has remained underexplored. In this volume, specialists in the field engage with a broad range of documentary sources. They discuss not only how various modes of communication, such as language, handwriting, and lay-out, are employed in specific contexts of writing, but also how these different modes are interrelated. Building on insights from contemporary social-semiotic theory, the volume makes a case for the establishment of historical social semiotics as a discipline.